Teaching and learning style preferences of Bachelor of Science in Criminology students in a state-funded university - Ocampo, Jiether M.; Torres, Kristelle Ann R. (Journal of Education and Learning (EduLearn), 2026)
The main objective of this study was to determine the learning and teaching style preferences of the Bachelor of Science or BS Criminology students using the descriptive-quantitative, comparative, and cross-sectional research design. The respondents of the study were the 271 BS criminology students during the second semester, academic year 2020-2021. The study utilized the self-constructed questionnaire as data gathering tool. Based on the analysis of the findings, it was concluded that most of the respondents moderately preferred the all-cited learning and teaching style preferences considered in the investigation. The analysis of respondents’ preferred learning and teaching styles when grouped according to their profile provided valuable insights into the variations and significance of these preferences across different demographic groups. By recognizing and adapting to these demographic differences, educators can create inclusive and effective learning environments that cater to the specific needs and preferences of students, ultimately enhancing their learning experiences and outcomes. To enhance the educational experience in the College of Criminal Justice Education, it is recommended to implement age-appropriate instructional strategies and create inclusive, gender-sensitive learning environments. This research can also be useful as a valuable resource to guide the future researches and contribute to the existing knowledge in the field.